Are changes in membrane lipids and fatty acid composition related to salt‐stress resistance in wild and cultivated barley?. Issue 2 (27th March 2013) - Chalbi, Najla; Hessini, Kamel; Gandour, Mhemmed; Mohamed, Salma Naeit; Smaoui, Abderrazek; Abdelly, Chedly; Youssef, Nabil Ben
Abstract The possibility to use membrane‐lipid measurements to screen barley genotypes for salt resistance was studied. The results showed that wild barley (Hordeum maritimum) displayed a typical halophytic response as compared to cultivated barley (Hordeum vulgare L. cv. Manel). Growth, tissue hydration, and photosynthetic activity were less affected by salinity in H. maritimum than in H. vulgare. The induced effects of long‐term NaCl treatment were reflected in root membrane lipids that remained relatively unchanged in wild barley, whilst they were significantly diminished with increasing salinity in H. vulgare. The levels of membrane‐lipid peroxidation and electrolyte leakage were changed only at high salt concentrations in H. maritimum whereas those of H. vulgare were considerably increased by lower salinity levels as a result of oxidative damage. These findings indicate that maintained membrane integrity (in H. Maritimum) may be considered a possible trait for salt resistance. However, membrane fluidity in H. vulgare was more increased than in H. maritimum. Thus, the unsaturated–to–saturated fatty acid ratio (UFAs : SFAs) and the double‐bond index (DBI), significantly increased in response to salt stress in cultivated barley while it did not change in H. maritimum. The changes in lipid unsaturation were predominantly due to increases in linolenic (C18:3), linoleic (C18:2), and oleic (C18:1) acids and decreases in stearic acid (C18:0). These results suggest that, in spite of being important for maintenance of membrane fluidity, the ability to increase unsaturation is not a determinant factor for salt resistance in barley species.